Tobacco workers tying the tobacco onto the poles for curing. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo made in the 1940s.
Tobacco workers tying the tobacco onto the poles for curing. This is also called stringing.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth